Higher Education Management in Academic Service to FKIP Student Satisfaction - Arozatulo Bawamenewi; Nathanael Sitanggang; Nasrun (Universitas Pendidikan Ganesha, 2022)
Higher education requires good management so that educational goals are achieved optimally. The research aims to analyze the management of tertiary institutions in developing academic services on student satisfaction. This study uses an approach with the case study method. The population in this study amounted to 2312 students. The method used in collecting data is the instrument. The research instrument is a questionnaire. The data analysis technique used in this research is a quantitative approach. The results showed student satisfaction for each study program, namely: Indonesian Language and Literature Education, with a satisfaction level of 82.9% and 17.1% dissatisfied. English education with a satisfaction level of 83.5% and 16.05% dissatisfied. Biology education with a satisfaction level of 78.2% and 21.8% dissatisfied. Mathematics education with a satisfaction level of 72.2% and 27.8% dissatisfied. Economic Education with a satisfaction level of 82.6% and 17.4% dissatisfied. PPKn with a satisfaction level of 75.5% and 24.5% dissatisfied. Based on the data analysis test using the SPSS version 26 program, the study’s results showed that student satisfaction with academic services was relatively good. The implications of this research are expected to improve the academic services provided to students.